2020
DOI: 10.17811/ebl.9.2.2020.97-105
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the board of directors and good governance practices

Abstract: Motivated by the debate on the adequacy of the composition of boards of directors, we examine the effect that board diversity has on corporate governance performance in Spain, analysing gender diversity, diversity of director types and tenure diversity. The findings reveal that diverse boards of directors have a positive influence on good governance practices,improving the efficiency of corporate governance mechanisms. These results could be interesting for practitioners and regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Nonetheless, female directors act as an efficient monitor to restrict tax aggressiveness. Consistent with the prior studies, we also argue that female director improves financial reporting quality (Adams & Ferreira, 2009) and promote good governance practices in an organization (Melón-Izco et al, 2020) through which they curb tax planning motives (Lanis et al, 2015;Richardson et al, 2016). However, the monitoring role of female directors in the presence of power CEOs is not very efficient over restricting aggressive tax planning.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Nonetheless, female directors act as an efficient monitor to restrict tax aggressiveness. Consistent with the prior studies, we also argue that female director improves financial reporting quality (Adams & Ferreira, 2009) and promote good governance practices in an organization (Melón-Izco et al, 2020) through which they curb tax planning motives (Lanis et al, 2015;Richardson et al, 2016). However, the monitoring role of female directors in the presence of power CEOs is not very efficient over restricting aggressive tax planning.…”
Section: Resultssupporting
confidence: 86%
“…Presence of women on board enhance economic outcomes (Reguera-Alvarado et al, 2017), higher sustainability disclosure (Ben-Amar et al, 2017), choose wellreputed external auditors (Lai et al, 2017) and pay more dividends to the shareholders (Ye et al, 2019) to restrict managers from extracting rents from free cash flows. Overall, female directors promote strong corporate governance practices in an organization (Melón-Izco et al, 2020). Accordingly, a negative link between female directorship and tax aggressiveness is evident in previous studies (Lanis et al, 2015;Richardson et al, 2016).…”
Section: Introductionmentioning
confidence: 64%
“…In recent years, many countries have paid special attention to diversity in the boardroom, which has been deemed as one of the indicators of good corporate governance practice (CGIO, 2012). Melón-Izco et al (2020) also found that board diversity shows the efficiency of corporate governance mechanism. Van Knippenberg et al, (2004) defined board diversity as ensuring heterogeneity among the directors.…”
Section: Introductionmentioning
confidence: 92%
“…Board size is the most significant characteristic that has been evidenced to influence the effectiveness of the boards. The vast majority of prior evidence supports the notion that large-sized boards are related to greater firm performance [49,63]. Liquidity is measured by the current ratio of firms [64].…”
Section: Research Variablesmentioning
confidence: 91%
“…Previous empirical studies on the influence of board diversity on company performance were inconsistent [49,50]. On the one hand, some studies reported the nexus of gender diversity and firm performance to be positive [9,20,21,24,25,27,40,[51][52][53].…”
Section: The Effect Of Gender Diversity On Firm Performancementioning
confidence: 99%